2020
DOI: 10.3390/en13092207
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Net Energy and Environmental Life-Cycle Assessment of the UK Electricity Grid

Abstract: National Grid, the UK’s largest utility company, has produced a number of energy transition scenarios, among which “2 degrees” is the most aggressive in terms of decarbonization. This paper presents the results of a combined prospective net energy and environmental life cycle assessment of the UK electricity grid, based on such a scenario. The main findings are that the strategy is effective at drastically reducing greenhouse gas emissions (albeit to a reduced degree with respect to the projected share of “zer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…In this study, in order to integrate the LCA and NEA approaches [10,12,13,15,17], when the EROI of electricity is calculated, all the energy investments at the denominator are accounted for in terms of their respective life-cycle CED, and they are expressed in units of oil-equivalent.…”
Section: Net Energy Analysis (Nea)mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, in order to integrate the LCA and NEA approaches [10,12,13,15,17], when the EROI of electricity is calculated, all the energy investments at the denominator are accounted for in terms of their respective life-cycle CED, and they are expressed in units of oil-equivalent.…”
Section: Net Energy Analysis (Nea)mentioning
confidence: 99%
“…Analysing the system as a whole is important because the grid's overall impacts depend not only on the technologies that comprise it, but also on the location, the specific electricity demand profile and the associated requirement for energy storage, as evidenced in recent analyses [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, in order to integrate the LCA and NEA viewpoints, and to maximize the consistency of the calculations, both internally and externally with some of the more recent literature [10,12,13,15,17], when calculating the EROI of electricity (either produced by a specific technology, or by the grid mix as a whole), all energy investments at the denominator are always accounted for in terms of their respective life-cycle CED (and are thus quantified in units of oil-equivalent).…”
Section: Net Energy Analysis (Nea)mentioning
confidence: 99%
“…It is also worth noting that it is important to assess each electricity grid as a whole, including all the electricity generation, transmission and storage technologies, and estimate the associated overall environmental impacts and energy implications, as discussed in some recent studies [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Reductions were also seen in the scenarios showing the modal shift for PM 10 and PM 2.5 (from 0.093 to 0.087 kg/day and 0.051 to 0.048 kg/day, respectively). Emissions relate to the carbon intensity of the electricity grid, and the increasingly renewable content of the UK grid mix (50% in 2019 [6]) means that considerable further reductions may be anticipated in future. Furthermore, the modelled scenarios also found that congestion levels decreased, resulting in reduced delays and shorter journey times for everyone across nine real world junctions (a 20% modal shift gave an 18.4 s reduction in delay averaged across all junctions improving to 39.8 s for a 50% modal shift).…”
Section: Introductionmentioning
confidence: 99%